Pengaruh Penyuluhan Metode Buku Bergambar Ilustrasi terhadap Pengetahuan Karies Gigi pada Anak Usia 10-12 Tahun di MIS Raudhatul Jannah Martapura - Puspita Sari, Ika; Kisworo Utami , Naning; Salamah, Siti; Danan, Danan (Poltekkes Kemenkes Banjarmasin, 2024)
Dental and oral health education is an effort made to change the behavior of a person, group of people, or society so that they have the ability and habit to behave healthily in the field of dental and oral health. Counseling using picture story books is an interesting way to convey information about health, especially dental and oral health, to children. This study aims to determine the effect of counseling using the illustrated picture book method on knowledge of dental caries in children aged 10-12 years at MIS Raudhatul Jannah Martapura. This type of research is quasi-experimental research with a one-group pretest-posttest design. The population in this study was 42 people. Sampling was done using the total sampling technique with 32 people as the number of respondents. The results showed that the average knowledge before counseling was 8.09 and after counseling was 8.84, representing an average increase in knowledge of 0.75. Paired Sample T-Test and Normality test were carried out, and the Wilcoxon Signed Rank Test indicated that there was a significant effect on dental caries knowledge after counseling using the illustrated picture book method, with a p-value of 0.001, which is less than the significance level (α) of 0.05. In conclusion, there is an effect of counseling using the illustrated picture book method on the knowledge of dental caries in children aged 10-12 years at MIS Raudhatul Jannah Martapura. For future researchers who want to research counseling using the illustrated picture book method, it is necessary to add modifications to the storyline to make it more appealing and creative, in order to attract children's interest and attention.